Faktor-faktor Yang Meningkatkan Harga Saham Perusahaan Food And Beverages: Studi Kasus Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Khim, Soei; Fadillah, Sultan Fajar; Muktiadji, Nusa (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
The capital market is a meeting place for two interests, namely those who need funds (companies) and those who have excess funds (investors). One of the capital market instruments, namely stocks, companies can get funds from investors by selling shares and investors can buy company shares to get profits in the future. The stock price of a company can be influenced by various factors including financial performance. Whether or not the company's financial performance can affect the rise or fall of the company's stock price. The better the company's performance, the better the opportunity to get a stock price increase in the future. This study aims to analyze the effect of Earning Per Share, Price Earning Ratio and Price Book Value on Stock Prices. The type of data used is secondary data and is a quantitative research. Sources of data obtained from the company's financial statements published on the company's website and the idx website. The population used is food and beverages sub-sector companies listed on the Indonesia Stock Exchange in 2016 - 2020. The sample used is 7 companies using purposive sampling. The analytical method used is multiple regression analysis using the SPSS version 22 program. The results showed that partially Earning Per Share, Price Earning Ratio and Price Book Value had a significant effect on stock prices. Simultaneously Earning Per Share, Price Earning Ratio and Price Book Value have a significant effect on stock prices Keywords: Earning Per Share, Price Earning Ratio, Price Book Value, and Stock Price.